`lim_(x->1)(f(x)-f(c))/(x-c)`

`lim_(x->1)(x^2 - x)/(x - 1)`

``Simplify:

`lim_(x->1)(x(x-1))/(x-1)`

`lim_(x->1)(x) = 1`

the alternate method to find the derivative of the function is the limit form.

**By limit process, the derivative of a function f(x) is :-**

**f'(x) = lim h --> 0 [{f(x+h) - f(x)}/h]**

Now, the given function is :-

f(x) = (x^2) - x

thus, `f'(x) = lim_(h -> 0) [{(x+h)^2 - (x+h) - {(x^2) - x}}/h]`

or, `f'x) = lim_(h -> 0) [{(h^2) + 2hx - h}/h]`

or, `f'(x) = lim_(h -> 0) [{2x + h - 1}]`

putting the value of h = 0 in the above expression we get

`f'(x) = 2x - 1`

Thus, `f'(c) = f'(1) = 2*1 - 1 = 1`

## We’ll help your grades soar

Start your 48-hour free trial and unlock all the summaries, Q&A, and analyses you need to get better grades now.

- 30,000+ book summaries
- 20% study tools discount
- Ad-free content
- PDF downloads
- 300,000+ answers
- 5-star customer support

Already a member? Log in here.

Are you a teacher? Sign up now